Candidate high-z protoclusters among the Planck compact sources, as revealed by Herschel–SPIRE. Issue 3 (11th January 2018) - Greenslade, J; Clements, D L; Cheng, T; De Zotti, G; Scott, D; Valiante, E; Eales, S; Bremer, M N; Dannerbauer, H; Birkinshaw, M; Farrah, D; Harrison, D L; et al.
Abstract: By determining the nature of all the Planck compact sources within 808.4 deg 2 of large Herschel surveys, we have identified 27 candidate protoclusters of dusty star-forming galaxies (DSFGs) that are at least 3σ overdense in either 250, 350, or 500 μ m sources. We find roughly half of all the Planck compact sources are resolved by Herschel into multiple discrete objects, with the other half remaining unresolved by Herschel . We find a significant difference between versions of the Planck catalogues, with earlier releases hosting a larger fraction of candidate protoclusters and Galactic cirrus than later releases, which we ascribe to a difference in the filters used in the creation of the three catalogues. We find a surface density of DSFG candidate protoclusters of (3.3 ± 0.7) × 10 −2 sources deg −2, in good agreement with previous similar studies. We find that a Planck colour selection of S 857 / S 545 < 2 works well to select candidate protoclusters, but can miss protoclusters at z < 2. The Herschel colours of individual candidate protocluster members indicate our candidate protoclusters all likely all lie at z > 1. Our candidate protoclusters are a factor of 5 times brighter at 353 GHz than expected from simulations, even in the most conservative estimates. Further observations are needed to confirm whether these candidate protoclusters are physical clusters, multiple protoclusters along the line of sight, or chance alignments of unassociated sources.